Governance, stewardship and sustainability theory, practice and evidence - Dallas, George S.; Lubrano, Mike (New York, NY Routledge, 2023)
The first introductory practical guide of its kind, this book brings together principles of corporate governance, investor stewardship, and enterprise sustainability in the context of institutional investment.

Stewardship codes are developing in diverse markets to provide a framework for responsible institutional investment practices and fiduciary duties for beneficiaries. While codes provide a starting point, the application of stewardship in practical terms can be challenging for many institutional investors. Written by two well-known corporate governance experts George Dallas and Mike Lubrano and based on the ICGN training course on stewardship that they developed, this book gives needed clarity, rigor, and guidance to practitioners about what we know - and don't know - about stewardship, governance and sustainability. It explores the theoretical foundations of stewardship, linking these to day-to-day decision making, providing real-life examples and practical tools on how to evaluate issues that arise for a company from an environmental, social and governance perspective and generate ideas about how to make investor stewardship a practical reality in similar cases.

Investor stewardship and ESG professionals, portfolio managers, senior managers, regulators, and finance students will appreciate this unique guide to develop, refine, and operationalize investor stewardship capabilities in line with the respected ICGN policy framework"
Foreword -- Preface to the second edition -- Preface to the first edition -- Background of the authors -- 1 Theory and Practice of Stewardship and Sustainability -- 2 Basic Principles of Corporate Governance: Investor Expectations and Corporate Realities -- 3 The Case for Stewardship and Sustainability: Ethics and Economics -- 4 Sources of ESG Data, Standards and Rating: Making Sense of them for Investors and Companies -- 5 ESG and Investment Decision-Making: Designing an Effective Methodology -- 6 Effective Stewardship in Practice: Monitoring, Engaging, Voting and Reporting -- 7 Company Perspective: Sustainability Governance and Reporting -- 8 Case Study : Volkswagen's DieselGate: Corporate Governance and Sustainability -- Index.
Includes bibliographical references and index.
Keywords: Corporate governance; Institutional investors; Social responsibility of business; Sustainable development; Corporations -- Investor relations